Evaluation of Factors Affecting Uricase Production by the Screened Wild/Natural Microbes - Harinath Dwivedi; Kusum Agrawal; Shubhini A Saraf (E-Journal of Chemistry)
Gout is a metabolic disorder due to the deposition of uric acid crystals within articular or periarticular tissues. Uricase (urate oxidase) catalyzes the oxidation of less water soluble uric acid (7 mg/dl) to a compound allantoin which is more water soluble(11g/L at 40°C) resulting into the ease of excretion of uric acid. The objective of the work was to develop a new method for screening of microbes for uricase production and estimation of uricase thereof. This was achieved by utilizing the fact that uric acid dissolves on being acted upon by uricase. The proposed method is a novel, inexpensive, simple and sensitive technique for screening and estimation of uricase. Biomass and uricase production at different stages of microbial growth curve for the uricase producing microbe was studied. Effects of different medium components affecting uricase production by microbes were studied using Placket Burman statistical design. Addition of uric acid in the nutrient medium was found to be effective in increasing the uricase production by microbes growing in the medium.